The First Electrical Resistivity Tomography Study Applied to an Ecuadorian Cave (Uctu Iji Changa, Tena): Insights into Amazonian Karst Systems - Chamba Vásquez, Bryan Antonio (2020)
The presence of carbonate rocks and high levels of precipitation have led to the ubiquitous formation of karstic caves in the Napo, region of Amazon in northeastern Ecuador, central part of the Subandean Zone. Caves such as these represent an important scientific target as they are typically well-suited for stratigraphical, geophysical, geochemical, and paleoclimate studies. Previous works have shown that resistivity surveys are a very efficient and appropriate way to detect and define shallow caves. However, no studies of this type have been conducted on Ecuadorian caves. Here, we present the first study of this kind from Ecuador. We show the results of applying the electrical resistivity tomography (ERT) technique to characterize the Uctu Iji Changa cave in the Napo province, Tena, Ecuador. The results from 13 survey lines show similar features pointing out three geologic layers: (1) a top layer of ~2 to 9-m-thick(< 50 Ωm - limestone); (2) a middle layer of ~2 to 4-m-thick (51–80 Ωm - marlstone), where our attention is focused for cave detection; (3) another limestone intercalation (< 50 Ωm); and a high-resistive anomaly (80 – >100 Ωm), related to signal from the cave. The ERT study was corroborated by speleological inspection of the cave to verify the results from the geophysical surveys. The ERT allowed us to determine the location and general geometry of the cave and to evaluate the accuracy of the method to determine shallow caves within the Amazon Karst System. In most survey lines, the resistivity contrast between the air-filled voids of the cave and the bedrock is high enough to define the approximate location and shape of the cavity. Our results demonstrate the efficacy of the ERT technique for the detection of shallow caves associated with karstic processes.